STRATEGI PERCEPATAN PENGEMBANGAN UPTD KPHP MODEL MERATUS DI KABUPATEN PENAJAM PASER UTARA PROVINSI KALIMANTAN TIMUR - Nasrudin Alamsyah (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
This study aims to determine, describe , analyze strategies to accelerate the development on UPTD KPHP Model Meratus in districts Penajam Paser Utara. This study used a qualitative approach with a view to gaining in-depth description of the issues related non- accelerated development UPTD KPHP Model Meratus in districts Penajam Paser Utara Province Kalimantan Timur. The data obtained was done by using interviews, observation and documentation, which is then analyzed using an interactive model through the stages of data reduction , data publishers and conclusion. Furthermore, the data and information collected was processed by diskriftif and SWOT analysis to determine the strategy in the development of the KPH . The results showed that the development UPTD KPHP Meratus Model , there are differences in perception among stakeholders. This is evidenced from the results of the SWOT analysis shows the differences in perspective in understanding some cases the problems in the development of KPH between Dinas Kehutanan Province and Dinas Kehutanan districts. Keywords: strategy, acceleration, development